THE ANALYSIS OF INTENTION TO BUY: AN EXTENDED THEORY OF PLANNED BEHAVIOR - Danu Gilang Pinasthika; Agus Suroso; Siti Zulaikha Wulandari (Journal of Management and Islamic Finance, 2021)
This research is aimed to test an empirical study on UNSOED Press. The study took the title: "The Analysis of Intention to Buy: An Extended Theory of Planned Behavior". The purpose of this research is to know and find empirical evidence of the influence of Brand Awareness, Price, Attitude, Subjective Norm, Perceived Behavioral Control of Purchase Intention. The population in this study were students in Universitas Jenderal Soedirman. The samples in this study were 211 person. Sample determination using the Convenience sampling method. The analysis tool used is multiple regression. Based on the results of the research and analysis of data shows that:(1) Brand Awareness has no effect on Purchase Intention. (2) Price has a positive effect on Purchase Intention. (3) Attitude has a positive effect on Purchase Intention. 4 Subjective Norm has no effect on Purchase Intention. 5 Perceived Behavioral control has a positive effect on Purchase Intention. The implication of the conclusion above is, UNSOED Press has to build awareness among students or target market. Promotion from faculty and lecturers must be improved. Lecturers can provide suggestions for using UNSOED Press during classroom learning. For the price, respondent said the price was not too expensive and have to maintance quality.